Potential Integration of Naqli and Aqli Knowledge in Counseling by Understanding the Concept of Wellness - Dini Farhana Baharudin; Mohd Rushdan Mohd Jailani; Zuria Mahmud; Salleh Amat (Universiti Sains Islam Malaysia, 2024)
Counseling is a profession that is concerned with all aspects of development for the individual client and this is synonymous with the philosophy of wellness. Even though the wellness emphasis is not well understood and is not systematically taught or applied due to ongoing debates among Western scholars about this concept and despite confusion with the usage of various terms to refer to wellness, the concept of wellness has the potential to be integrated with the naqli and aqli knowledge in counseling. In Islam, this concept has long been discussed. It is hoped that by comparing the Islamic concept of welness to the Western perspective would help increase the understanding of this concept and highlight its application in counseling as an example of the integration of revealed knowledge and rational science. This paper will discuss briefly the concept of wellness from the perspective of Islam and the West, as well as looking at some common grounds and differences between the two views. Both views agree that wellness is a lifelong process that is holistic, comprising of multiple dimensions. However, the Islamic view of this concept is broader and complements the existing view on wellness. The implication of this study to the field of counseling includes refocusing counseling to the developmental aspect of an individual that comprised of not only remediation but also prevention.